Migraine and tinnitus: implications for multidisciplinary management - Leonel, Vitória Carolina; Pradela, Juliana; Zamberlan-Amorim, Nelma Ellen; Rodrigues, Amanda; Reis, Ana Cláudia Mirândola Barbosa; Dach, Fabiola; Grossi, Debora Bevilaqua (Headache Medicine, 2024)
IntroductionPatients with migraines often experience vestibular and audiological symptoms, especially tinnitus. Both conditions are linked to vertigo, neck pain, and depression, which can affect the disease burden.ObjectiveTo examine the correlation between tinnitus characteristics and disability with measures of disability, central sensitization, and depression in migraine patients.MethodsForty-six women with migraine and tinnitus (aged 18-55 years) were recruited. All participants underwent audiological evaluations to exclude hearing loss and acuphenometry assessments to determine tinnitus intensity (dB) and frequency (Hz). Questionnaires administered included the Tinnitus Handicap Inventory (THI), Headache Impact Test (HIT-6), Central Sensitization Inventory (CSI), Neck Disability Index (NDI), Patient Depression Questionnaire (PHQ-9), and Dizziness Handicap Inventory (DHI). Spearman correlations were classified as weak (rho